Rice Green Revolution in Sub-Saharan Africa - Otsuka, Keijiro; Mano, Yukichi; Takahashi, Kazushi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This open access book seeks effective strategy to realize a rice Green Revolution in sub-Saharan Africa based on more than ten years of research team$1 (Bs inquiries into determinants and consequences of new technology adoption in rice farming in seven countries in this region. Rigorous statistical analyses are carried out by using valuable household data of rice farmers. The book is actually sequel to the two earlier books on the same subject published by Springer and edited by K. Otsuka and D.F. Larson, An African Green Revolution published in 2013 and In Pursuit of an African Green Revolution in 2016. The main message of the first book was that rice is the most promising cereal crop in SSA because of the high transferability of Asian rice technology, whereas that of the second book was that rice cultivation training programs are effective in significantly increasing rice yield in SSA. This third book has wider coverage in terms of topics, study periods, and study sites. It continues toshow the significant impacts of rice cultivation training on productivity and newly demonstrates the high sustainability of the productivity impact of the training and the existence of spillover effects from trainees to other farmers by using panel data. We newly assess the important role of mechanization in intensification of rice farming, high returns to large-scale irrigation schemes, and the critical role of rice millers in improving the quality of milled rice. Based on these studies, this book provides clear pathways toward full-fledged Green Revolution in rice farming in sub-Saharan Africa.s
Chapter 1. The Rice Green Revolution in sub-Saharan Africa: Issues and opportunities -- Chapter 2. The Role of Extension in the Green Revolution -- Chapter 3. The Case of Cote d$1 (BIvoire: Learning from Experts of Rice Farming Management and Peer Farmers about Rice Production -- Chapter 4. The Case of Tanzania: Effectiveness of Management Training on Rice Framing and Farmer-to-Farmer Extension -- Chapter 5. The Case of Uganda: Long-term and Spillover Effects of Rice Production Training -- Chapter 6. The Case of Mozambique: The Importance of Management Training for Rice Farming in Rainfed Areas -- Chapter 7. Intensification of Rice Farming: The Role of Mechanization and Irrigation -- Chapter 8. Mechanization in Cote d'Ivoire: Impacts of Tractorization on Agricultural Intensification -- Chapter 9. Mechanization in Tanzania: Impact of Tractorization on Intensification and Extensification of Rice Farming -- Chapter 10. Irrigation in Kenya: Economic Viability of Large-scale Irrigation Construction -- Chapter 11. Irrigation Scheme Size and its Relationship to Investment Return: The Case of Senegal River Valley -- Chapter 12. Rice Milling in Kenya: An Inquiry into the Process of Upgrading Rice Milling Services -- Chapter 13. Toward Quality Upgrading of Rice Production in SSA:Experimental Evidence from Northern Ghana -- Chapter 14. Toward a Full-Fledged Rice Green Revolution in Sub-Saharan Africa.s
Keywords: Agriculture -- Economic aspects; Economic development; Development economics; Agriculture; Africa -- Economic conditions; Agricultural Economics; Development Studies; Development Economics; Agriculture; African Economics